2016
DOI: 10.1053/j.ajkd.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Access to and Outcomes of Kidney Transplantation in Children, Adolescents, and Young Adults: Results From the ESPN/ERA-EDTA (European Society of Pediatric Nephrology/European Renal Association−European Dialysis and Transplant Association) Registry

Abstract: We believe this is the first study examining racial differences in access to and outcomes of kidney transplantation in a large European population. We found important differences with less favorable outcomes for black and Asian patients. Further research is required to address the barriers to optimal treatment among racial minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 36 publications
5
44
2
4
Order By: Relevance
“…Similar to findings by Patzer et al, Hispanic patients showed a significantly lower likelihood of transplantation compared to whites, but mainly in the older age group of 19–20 years (3). Prior studies have suggested that possible reasons contributing to racial-ethnic differences in access to kidney transplants beyond socio-economic differences were decreased access to living related donors, potential physician racial bias in belief of treatment success and life value, socio-cultural beliefs regarding transplants, lack of education, social support or parental oversight assisting with treatment adherence, and worse pre-dialysis care (3, 25). …”
Section: Discussionmentioning
confidence: 99%
“…Similar to findings by Patzer et al, Hispanic patients showed a significantly lower likelihood of transplantation compared to whites, but mainly in the older age group of 19–20 years (3). Prior studies have suggested that possible reasons contributing to racial-ethnic differences in access to kidney transplants beyond socio-economic differences were decreased access to living related donors, potential physician racial bias in belief of treatment success and life value, socio-cultural beliefs regarding transplants, lack of education, social support or parental oversight assisting with treatment adherence, and worse pre-dialysis care (3, 25). …”
Section: Discussionmentioning
confidence: 99%
“…Black and Hispanic adults treated with dialysis have been shown to have longer survival compared with non-Hispanic white adults, despite potential adverse social and socioeconomic positions that may predispose to poorer health outcomes, including lower access to transplantation. [8][9][10][11]24,26,29,[31][32][33] Although studies in the pediatric population have also shown marked disparities in access to transplantation in non-Hispanic black and Hispanic children and worsened graft survival in non-Hispanic black children, 24,26,29,34 our study is novel in its focus on the risk of death by race and ethnicity in children treated with dialysis and transplantation using data from a large United States cohort. We found that the risk of death was significantly higher in non-Hispanic black children beginning RRT compared with non-Hispanic white children but that access to transplantation seemed to mediate the differential risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…24,28 A recent European registry study of children treated with RRT suggested a trend toward lower risk of death in black children, although few black children were included in the study, and the observation did not achieve statistical significance. 29 A prior study using the US Renal Data System (USRDS) suggested a higher relative risk of death in black versus white children treated with dialysis, 30 but the focus of this study was not on racial disparities and their potential explanatory factors. Because children have ready access to health care, higher priority on the transplant waitlist than most adults, and fewer comorbid conditions, which may reduce the potential for confounding, the study of racial disparities in the survival of children may be informative to our overall understanding of differences in mortality outcomes by race.…”
mentioning
confidence: 96%
“…Although much of the research at the intersection of healthcare and race is conducted in the United States [20], the situation of minority groups is likely to be similar in Europe [10]. For instance, a large European study on end-stage renal disease demonstrated that "black and Asian patients were about half as likely to receive a kidney transplant as white patients, a finding that was not explained by differences in cause of kidney failure" [21]. The authors highlighted that disparities, both in terms of mortality on renal replacement therapy and decreased access to renal transplantation, could not be explained completely by the cause of kidney failure, and that other factors such as the socioeconomic, cultural, environmental and even other biological factors were likely to be involved [21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a large European study on end-stage renal disease demonstrated that "black and Asian patients were about half as likely to receive a kidney transplant as white patients, a finding that was not explained by differences in cause of kidney failure" [21]. The authors highlighted that disparities, both in terms of mortality on renal replacement therapy and decreased access to renal transplantation, could not be explained completely by the cause of kidney failure, and that other factors such as the socioeconomic, cultural, environmental and even other biological factors were likely to be involved [21]. Moreover, it is worrying that little is known on the epidemiological profile of minority groups in European high-income countries due to their often unfortunate exclusion in epidemiological studies [22].…”
Section: Introductionmentioning
confidence: 99%